A preliminary study on upstream migration of mangroves in response to changing environment along River Hooghly, India. (February 2020) - Ghosh, Somdeep; Bakshi, Madhurima; Gupta, Kaushik; Mahanty, Shouvik; Bhattacharyya, Subarna; Chaudhuri, Punarbasu
Abstract: Environmental changes and anthropogenic activities can be linked to altered distribution and abundance of species. However, the ecological impacts of change in the microenvironment have not been well documented. Herein, we have identified the distribution of mangroves and associated species and characterized surface sediment and water samples along the banks of River Hooghly. The application of Combined Mangrove Recognition Index (CMRI) and its validation with the available ground data on satellite image of 2015 indicates that some mangrove species have reclaimed the upper course of the river, which was earlier absent before 1995. This study is the first report on the upstream migration of mangrove species such as Sonneratia caseolaris, Sonneratia apetala, Derris trifoliata, Hibiscus tiliaceus, and Thespesia populnea in River Hooghly. The changes in pollution load, varied sedimentation pattern, high chemical oxygen demand, mean sea-level rise, and anthropogenic activity might have played a significant role in the upstream migration of mangroves. Highlights: First ever report of migration of mangroves in upstream of river Hooghly. NDVI reveals mangrove species have reclaimed the upper course of the river which was earlier absent before 1995. Slight increment in pollution load of the river. Several natural and anthropogenic factors are behind this migration of mangroves.